Recombinant protein production data after expression in the bacterium Escherichia coli - Cantú Bustos, Jesús Enrique; Cano del Villar, Kevin D.; Vargas Cortez, Teresa; Morones Ramírez, José Rubén; Balderas Rentería, Isaías; Zárate Kalfópulos, Xristo (2016)
Fusion proteins have become essential for the expression and purification of recombinant proteins in Escherichia coli. The metalbinding protein CusF has shown several features that make it an attractive fusion protein and affinity tag: "Expression and purification of recombinant proteins in Escherichia coli tagged with the metalbinding protein CusF" (Cantu-Bustos et al., 2016 [1]). Here we present accompanying data from protein expression experiments; we tested different protein tags, temperatures, expression times, cellular compartments, and concentrations of inducer in order to obtain soluble protein and low formation of inclusion bodies. Additionally, we present data from the purification of the green fluorescent protein (GFP) tagged with CusF, using Ag(I) metal affinity chromatography